Sustainable Aloe vera/chitosan-based edible coatings reduce postharvest loss of stored fresh figs (Ficus carica L.) - Kaur, Navjot; Somasundram, Chandran; Razali, Zuliana; Ahmed, Zienab Fawzy Reiad (Frontiers in Sustainable Food Systems, 2024)
Fresh fig fruits are abundant sources of antioxidants and health-beneficial compounds. However, they are highly prone to spoilage and have short postharvest life. Thus, the current study aimed to investigate the potential synergistic effect of applying Aloe vera (AV) gel combined with chitosan (CH) as a natural edible coating on fresh fig fruits' quality and shelf life. Different coating treatments; T1-Water; T2-CH (0.5%, w/v); T3-AV (100%); T4-AV (100%) + 1% CH (25:75, v/v); T5-AV (50%) + 1% CH (25:75, v/v); T6-AV (50%) + 1% CH (40:60, v/v)), were applied to fresh fig fruits utilizing dip method. Fruits were analyzed weekly to examine fruit weight loss, decay, color, texture, enzyme activity (β Galactosidase and polyphenol oxidase enzyme (PPO)), phenolic content, antioxidants, and microbial load. The combined AV and CH coatings extended the shelf life of the fig fruits up to 21 days compared to the control during storage at 2°C and 90-95% R.H. The T5 treatment has significantly retarded the fruit decay, reduced total fungal and bacterial counts, preserved total phenolics and flavonoid contents, and antioxidant activity (enzymatic and nonenzymatic), as compared to the other treatments. Meanwhile, T6 fruits showed minimum fruit weight loss and microbial load. These treatments can be applied at a large scale to improve the shelf life of fresh fig fruits.